Pronoun beta and ose in Moluccas Malay - Kopong, Richard; Imbang, Djeinnie; Tulung, Golda J.; Pamantung, Rina P. (Linguistics and Culture Review, 2022)
Moluccas Malay is generally spoken in Moluccas and North Moluccas Provinces. However, every place in those provinces has its own different vocabulary usage of the language like in Tanimbar Archipelago Regency. One of the differences can be seen by the usage of pronouns, especially the first person singular beta and the second person singular ose. In Tanimbar, beta is usually changed to saya and sa, while ose is usually changed to kau, engko, itrana, and itwata. In another place like Ambon, ose is sometimes changed to ale. In addition to regional differences, different situations also affect changes in the use of the two pronouns. This is analyzed by using the acronym SPEAKING in anthropological linguistics to be able to find out the speech situation such as place, time, speaker and addressee, purpose, act sequence of the speech, and others. Research data were collected using observation, interview, and documentation techniques which were then analyzed using data reduction, data display, and data conclusion. The results showed that the rules for using the pronouns beta and ose depend on different situations such as in the family when meeting new people, differences in age, gender, social groups.